2012
DOI: 10.1039/c1cc16213f
|View full text |Cite
|
Sign up to set email alerts
|

Advanced fabrication of metal–organic frameworks: template-directed formation of polystyrene@ZIF-8 core–shell and hollow ZIF-8 microspheres

Abstract: The conjunction of porous ZIF-8 with polystyrene spheres is demonstrated to induce the formation of polystyrene@ZIF-8 core-shell structures. A subsequent etching process on polystyrene@ZIF-8 core-shells to remove polystyrene cores results in a unique hollow ZIF-8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
198
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(208 citation statements)
references
References 39 publications
7
198
1
Order By: Relevance
“…Considering that SPS may decompose completely after pyrolysis at temperature of above 400 °C (see thermogravimetric (TG) curve of SPS in Figure S1), the annealing treatment of SPS@MoS 2 at 800 °C could generate a hollow MoS 2 . [31][32][33] Nonetheless, the confi ning effect of MoS 2 shells probably leads to incomplete decomposition of SPS core. In other words, a small amount of porous carbon may be left inside the MoS 2 shell, which will be validated from the following various forms of characterization on the ultimate product.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that SPS may decompose completely after pyrolysis at temperature of above 400 °C (see thermogravimetric (TG) curve of SPS in Figure S1), the annealing treatment of SPS@MoS 2 at 800 °C could generate a hollow MoS 2 . [31][32][33] Nonetheless, the confi ning effect of MoS 2 shells probably leads to incomplete decomposition of SPS core. In other words, a small amount of porous carbon may be left inside the MoS 2 shell, which will be validated from the following various forms of characterization on the ultimate product.…”
Section: Resultsmentioning
confidence: 99%
“…However, nanoparticles (NPs) tend to dissolve or agglomerate under the acidic environment created by the dissociation of ligands during this solution process. Therefore, surface modification is required to initiate the nucleation and growth of the MOFs around the nanoparticle 27,[35][36][37][38][39][40][41][42] . But, the direct nucleation of MOF crystals in the growth solution is not prevented.…”
mentioning
confidence: 99%
“…Furthermore, the aforementioned nanoparticles are limited to solid inorganics and polymers that are several to hundreds of nanometres in size 27,[33][34][35][36][37][38][39][40][41][42][43][44] . Hence, the direct encapsulation of ions, inorganic and organic materials as well as bioactive proteins in MOFs at room temperature, without limiting the size, shape and classification and with a short processing time, should ultimately yield functional MOF composite thin films for a wide variety of purposes 47 .…”
mentioning
confidence: 99%
“…However, the low mechanical strength and block nature of the MOF products greatly prevent their application in these certain areas. To overcome this issue, great efforts have been made on designed synthesis of novel-type composites of MOFs with polymers or nanocarbons in recent years [8][9][10]. For instance, Schwab et al [11] reported the in situ immobilisation of a MOF (HKUST-1) into a hydrophilized macroporous polyHIPE monolith, and revealed that the resulting HKUST-1@polyHIPE composites effectively combines the macroporosity of the polyHIPE with the microporosity of the crystalline MOF of HKUST-1, which is an attractive combination for applications where diffusion processes are limiting.…”
Section: Introductionmentioning
confidence: 99%